Expression and Clinical Significance of the m6A RNA-Binding Proteins YTHDF2 in Peripheral Blood Mononuclear Cells From New-Onset Ankylosing Spondylitis - Luo, Qing; Guo, Yongqin; Xiao, Qiuyun; Fu, Biqi; Zhang, Lu; Guo, Yang; Huang, Zikun; Li, Junming (Frontiers in Medicine, 2022)
The study has focused on determining the association of m6A methyltransferase (METTL3, MTEEL14, WTAP), demethylase (FTO, ALKBH5), RNA-binding proteins (YTHDF2) and ankylosing spondylitis (AS). A total of 154 specimens, containing 79 new-onset AS patients and 75 healthy controls (HC), participated in the study. The mRNA expressions of these m6A methyltransferase, demethylase, and RNA-binding protein in peripheral blood mononuclear cells (PBMC) were detected by quantitative real-time PCR (qRT-PCR). The data showed that the mRNA expressions of YTHDF2 and ALKBH5 in PBMC from new-onset AS patients were significantly decreased and there was a positive correlation between RNA-binding proteins (YTHDF2) and demethylase (ALKBH5) in new-onset AS patients. Logistic regression analysis demonstrated that the expression of YTHDF2 mRNA in PBMC is a risk factor of AS. Receiver operating characteristic (ROC) analysis the area under the curve (AUC) for mRNA YTHDF2 in new-onset AS and HC was 0.692, with a cut-off of <0.8724, a sensitivity of 67% and a specificity of 63%. Moreover, We constructed a novel predictive model based on combination of mRNA YTHDF2 and systemic immune-inflammation index (SII) for AS diagnosis (AUC=0.865, sensitivity=79.45%, specificity=84.00%) and the predictive model correlated with the activity and severity of AS. The present study indicates that the mRNA expression of YTHDF2 in PBMC may be involved in AS pathogenesis and predictive model based on combination of mRNA YTHDF2 and SII act as marker for diagnosis and progression of diseases.